Comparison of surgical clipping and endovascular coiling in the treatment of oculomotor nerve palsy caused by posterior communicating artery aneurysm. Issue 47 (20th November 2020) - Liu, Jianwu; Peng, Chengfu; Zhu, Guofeng; Sheng, Chunpeng; Song, Shuxin; Cheng, Zhihua; Zhu, Jianming
Abstract : Abstract: Oculomotor nerve palsy (ONP) caused by posterior communicating aneurysm (PcomAA) is mainly treated by surgical clipping or endovascular coiling. However, there are still some controversies about which treatment method could provide the more beneficial prognosis. This study aimed to compare ONP recovery rate between surgical clipping and endovascular coiling in patients diagnosed as PcomAA combined with ONP, and explore the potential risk factors of ONP recovery. The clinical data of 152 patients with ONP caused by PcomAA were retrospectively analyzed. Diameter of aneurysm, different treatment methods (surgical clipping or endovascular coiling), subarachnoid hemorrhage (SAH), degree of preoperative ONP, time from ONP onset to treatment, as well as degree of ONP symptom recovery were collected from medical records. All patients were followed up for at least 1 year. One hundred twelve patients underwent surgical clipping and 40 patients received endovascular coiling. There were no significant differences in age, gender, aneurysm diameter, hypertension, dyslipidemia, time from ONP symptom onset to treatment, SAH, and preoperative ONP degree between the 2 groups (all P  > .05). Time to complete or partial recovery was 86.7 ± 35.7 days for patients receiving surgical clipping and 132.6 ± 37.5 days for patients receiving endovascular coiling, respectively (Log rank test, P  < .001). The recovery rate was 94.6% in the surgical clipping group and 65.0% in the endovascular coiling group. The difference between the two groups was statistically significant ( P  < .001). Postoperative ONP recovery in the surgical clipping group was significantly superior to that of patients in the endovascular coiling group (HR, 2.625; 95% CI: 1.423–4.841; P = .002). Time from ONP symptom onset to treatment exerted the obvious effect on the ONP prognosis (HR, 0.572; 95% CI: 0.384–0.852; P  = .006). In addition, the ONP recovery in patients with SAH before surgery was also independently associated with ONP prognosis (HR, 1.276; 95% CI, 1.043–1.562; P  = .018). There was no treatment-related death in either group, and postoperative complications were within the manageable range. The recovery rate and recovery degree of ONP after surgical clipping was significantly better than that of endovascular coiling in PcomAA patients combined with ONP. The postoperative ONP recovery was associated with preoperative spontaneous SAH and time from ONP onset to treatment.